Rückenschmerz: gezielte Anamnese und klinische Untersuchung - Chenot, Jean-François (DMW - Deutsche Medizinische Wochenschrift, 2018)
Low back pain is common, but serious underlying disorders are infrequent in ambulatory care. Extensive diagnostic testing is neither feasable nor reasonable due to epidemiological and economical considerations. A structured step wise approach allows to differentiate between specific and unspecific low back pain.
Keywords: Kreuzschmerzen; körperliche Untersuchung; diagnostische Tests